Application Of The Group Investigation Model, Using Whatsapp To Increase Learning Outcomes For Class VI Students Of Sd Negeri Trayu Samigaluh Academic Year 2020/2021 - Erma Widyaningsih (International Journal of Chemistry Education Research, 2022)
The purpose of this study was to improve learning outcomes for grade VI students at SD Negeri Trayu Samigaluh Kulon Progo for the 2020/2021 school year and the ability of teachers to manage learning through the application of the Group Investigation model with WhatsApp Group Classes. This research is a classroom action research. This research was carried out in two cycles, in which each cycle had two meetings covering planning, action, observation, and reflection. The research subjects were students of Class VI SD Negeri Trayu Samigaluh, Kulon Progo Regency. Data and data sources come from students, and the learning process. Data collection techniques through observation and tests. Data analysis with qualitative descriptive technique. The results showed that the application of the Group Investigation model using the WhatsApp Group class could improve the learning outcomes of grade VI students at SD Negeri Trayu Samigaluh for the 2020/2021 school year. It can be seen the increase in cognitive test scores from 35.29% (cycle I) to 58.82% (cycle II). Furthermore, in the management of learning by teachers, the average result was 3.49 (cycle I), with the category "Very Satisfactory", while in Cycle II the average value was obtained at 3.74 with the category "Very Satisfactory".